2020
DOI: 10.3174/ajnr.a6671
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy Associated with Severe COVID-19 Infection: Sequela of Hypoxemia?

Abstract: There is increasing evidence to suggest that complications of coronavirus disease 2019 (COVID-19) infection are not only limited to the pulmonary system but can also involve the central nervous system. Here, we report 6 critically ill patients with COVID-19 infection and neuroimaging findings of leukoencephalopathy. While these findings are nonspecific, we postulate that they may be a delayed response to the profound hypoxemia the patients experienced due to the infection. No abnormal enhancement, hemorrhage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 20 publications
4
67
0
4
Order By: Relevance
“…We found that white matter abnormalities was the most frequent neuroimaging pattern in patients with COVID-19 and neurological manifestations, which is consistent with a previous review (37). White matter-specific injuries was presented in a case series of six COVID-19 patients who exhibited an altered mental status (38). MRI revealed FLAIR hyperintensities in bilateral deep white matter in all six patients, corpus callosum in one patient, middle cerebellar peduncles in five patients, and corticospinal tracts in three patients (38).…”
Section: White Matter Abnormalitysupporting
confidence: 91%
See 1 more Smart Citation
“…We found that white matter abnormalities was the most frequent neuroimaging pattern in patients with COVID-19 and neurological manifestations, which is consistent with a previous review (37). White matter-specific injuries was presented in a case series of six COVID-19 patients who exhibited an altered mental status (38). MRI revealed FLAIR hyperintensities in bilateral deep white matter in all six patients, corpus callosum in one patient, middle cerebellar peduncles in five patients, and corticospinal tracts in three patients (38).…”
Section: White Matter Abnormalitysupporting
confidence: 91%
“…White matter-specific injuries was presented in a case series of six COVID-19 patients who exhibited an altered mental status ( 38 ). MRI revealed FLAIR hyperintensities in bilateral deep white matter in all six patients, corpus callosum in one patient, middle cerebellar peduncles in five patients, and corticospinal tracts in three patients ( 38 ). A case series reported four children infected by SARS-Cov-2 with mild respiratory symptoms and neurological symptoms such as encephalopathy and proximal muscle weakness, and the common neuroimaging pattern was hypointensity on CT and hyperintensity with restricted diffusion on T2 MRI in the splenium of the corpus callosum, known as cytotoxic lesion of the corpus callosum (CLOCC), which is a rare but reversible lesion ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Although the current literature is limited regarding neuroimaging findings in patients with COVID-19, [6][7][8] there have been recent reports of critically ill patients with leukoencephalopathy with or without cerebral microhemorrhages. [9][10][11][12][13][14] Different radiologic patterns of white matter (WM) injury have been described in critically ill patients with viral infections, including diffuse leukoencephalopathy with microhemorrhages, acute disseminated encephalomyelitis (ADEM), and posterior reversible encephalopathy syndrome (PRES). 11,[15][16][17][18][19][20] Due to a paucity of neuropathologic data, the pathophysiologic processes responsible for these imaging characteristics are not completely understood.…”
mentioning
confidence: 99%
“…At the time of this survey, only half of COVID-19 wards had chosen to implement a regular follow-up of patients discharged alive, even though it is possible that a follow-up was put in place more extensively later than when this survey was conducted, when hospitals were too busy with the organization and immediate delivery of acute care to be able to implement regular follow-up for those discharged. This view is supported by the small number of publications available till now on the follow-up and clinical state of patients who survived COVID-19 [5] , often limited to specific conditions [6] . Given the array of body systems affected by the virus, it will be paramount to describe to which extent COVID-19 patients have recovered and which sequelae they suffer from.…”
mentioning
confidence: 99%